Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Bank BPR Supradanamas Cabang Jakarta Barat: The Influence of Leadership Style and Work Motivation on Employee Performance at Bank BPR Supradanamas West Jakarta Branch - Dodi Prasetiyo; Nurhadi Nurhadi; Seno Sudarmono Hadi (CV Warnak Johanna Nusantara, 2025)
Branch, West Jakarta. Human resources are an important factor in an organization to achieve goals through increased work productivity. The purpose of this study was to determine the influence of leadership style and work motivation on employee performance at Bank BPR Supradanamas, Jelambar Branch, West Jakarta. This study uses a quantitative descriptive method with data collection techniques in the form of questionnaires distributed to 40 respondents. The results showed that leadership style had a positive and significant effect on employee performance, with a significance value of 0.000 <0.05 and a t-count value of 3.463> t table 2.024. Work motivation also had a positive and significant effect on employee performance, indicated by a significance value of 0.000 <0.05 and a t-count value of 3.647> t table 2.024. Simultaneously, leadership style and work motivation have a significant effect on employee performance, as evidenced by the calculated F value of 40.804> F table 3.24 and a significance of 0.000 <0.05. The coefficient of determination (Adjusted R²) value of 0.671 indicates that 67.1% of the variation in employee performance can be explained by the two independent variables, and the remaining 32.9% is explained by other variables outside the model